Quantitative Electrocardiographic Measures, Neuromuscular Disorders, and Survival in Left Ventricular Hypertrabeculation/Noncompaction. Issue 3 (28th May 2013) - Stöllberger, Claudia; Gerger, Daniel; Wegner, Christian; Finsterer, Josef
<x xml:space="preserve">Abstract</x> Background Left ventricular hypertrabeculation/noncompaction (LVHT) is frequently associated with neuromuscular disorders (NMDs) and electrocardiographic (ECG) abnormalities. Quantitative ECG‐measures (QEMs) are risk markers for mortality in cardiomyopathies. We measured QEMs in the ECGs in LVHT patients with and without NMDs. Methods Included were patients in whom (a) LVHT was diagnosed between 1995 and 2011 and (b) baseline ECG recordings were available. All underwent a clinical examination and were invited for a neurological investigation. QRS duration, QT, QTc and PR intervals were analyzed. Survival status was assessed in June 2011. Results In 141 patients (mean age 54 years, 49 females) QRS duration ranged from 40 to 200 ms, a QRS duration >120 ms was found in 19% and was associated with increased age, heart failure, left ventricular dilatation and systolic dysfunction (P < 0.001). QT intervals ranged from 240 to 600 ms. The QTc intervals ranged from 302 to 612 ms, a QTc interval >440 ms was found in 38% and was associated with left ventricular dilatation and systolic dysfunction (P < 0.001). PR intervals ranged from 90 to 360 ms, a PR interval >200 ms was found in 16% and associated with left ventricular dilatation (P < 0.01). No QEM differences were found in 86 patients with and 13 without NMD. During 59 months follow‐up 45 patients died. QEMs were no mortality predictors, whereas multivariate analysis identified heart failure (P < 0.01), atrial fibrillation (P < 0.01) and diabetes mellitus (P < 0.05) as mortality predictors. Conclusions Prolonged QRS complexes, PR and QTc intervals in LVHT are associated with heart failure and left ventricular dilatation, but not with NMD. The prognostic role of QEMs in LVHT needs further investigations in larger series.